The Use of WhatsApp Groups as A Means of Health Education for Young Women About the First Thousand Days of Life (1000 HPK) - Yuli Admasari; Sri Restu Tempali; Mercy Joice Kaparang (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The growth and development of children is the fundamental thing that determines the future of a nation. One of the problems facing developing countries is stunting. The impact of stunting can increase the incidence of pain and death, motor, and verbal disorders, the risk of developing generalized diseases, and decreased productivity and work capacity. Interventions are prepared early, especially for adolescents, namely providing education for the First 1000 Days of Life (HPK) to young women through digital education which is currently being promoted. The study aims to prove the effectiveness of using WhatsApp Groups as a health education medium in young women with about 1000 HPK. The research method is quasi-experimental with one group removing treatment design which will be carried out in April–June 2022. The number of samples of 100 students in grades 11 and 12 at SMAN in the Palu city area was taken with cluster-stratified sampling techniques. The data were analyzed with a univariate test and a bivariate test using the Wilcoxon test. The results of the analysis showed that there was an increase in the average value of knowledge before and after treatment was 45.63 with p = 0.000 and there was an increase in the average attitude value before and after treatment was 42.49 with p = 0.000. This shows that the use of WhatsApp Groups as a health education medium is effective in increasing the knowledge and attitudes of young women by about 1000 HPK. It is hoped that the use of WhatsApp Groups will be increasingly used in health education by about 1000 HPK. Abstrak: Pertumbuhan dan perkembangan anak adalah hal mendasar yang menentukan masa depan suatu bangsa. Salah satu masalah yang dihadapi negara berkembang adalah stunting. Dampak stunting dapat meningkatkan kejadian kesakitan dan kematian, gangguan motorik, verbal, resiko terkena penyakit digeneratif, menurunya produktivitas dan kapasitas kerja. Intervensi dipersiapkan secara dini terutama saat remaja yaitu memberikan pendidikan 1000 Hari Pertama Kehidupan (HPK) pada remaja putri melalui digital education yang saat ini sedang digalakan. Tujuan penelitian untuk membuktikan efektifitas pemanfaatan  whatsapp groups sebagai media pendidikan kesehatan pada remaja putri tentang 1000 HPK. Metode penelitian adalah  quasi eksperiment dengan one group remove treatment design yang dilaksanakan pada bulan April–Juni 2022. Jumlah sampel 100 siswi kelas 11 dan 12 di SMAN wilayah kota Palu yang diambil dengan tehnik clusterstratified sampling. Data dianalisis dengan uji univariat dan uji bivariate menggunakan uji Wilcoxon. Hasil analisis menunjukan terdapat peningkatan rata-rata nilai pengetahuan sebelum dan sesudah perlakuan adalah 45,63 dengan p=0,000 serta terdapat peningkatan rata-rata nilai sikap sebelum dan seduah perlakuan adalah 42,49 dengan p=0,000. Hal ini menunjukan bahwa pemanfaatan whatsapp groups sebagai media pendidikan kesehatan efektif untuk meningkatkan pengetahuan dan sikap remaja putri tentang 1000 HPK. Diharapkan penggunaan whatsapp group semakin gencar dimanfaatkan dalam pendidikan kesehatan tentang 1000 HPK.